A genome-wide association study in multiple system atrophy. (11th October 2016) - Sailer, Anna; Scholz, Sonja W.; Nalls, Michael A.; Schulte, Claudia; Federoff, Monica; Price, T. Ryan; Lees, Andrew; Ross, Owen A.; Dickson, Dennis W.; Mok, Kin; Mencacci, Niccolo E.; Schottlaender, Lucia; et al.
Abstract : Objective: To identify genetic variants that play a role in the pathogenesis of multiple system atrophy (MSA), we undertook a genome-wide association study (GWAS). Methods: We performed a GWAS with >5 million genotyped and imputed single nucleotide polymorphisms (SNPs) in 918 patients with MSA of European ancestry and 3, 864 controls. MSA cases were collected from North American and European centers, one third of which were neuropathologically confirmed. Results: We found no significant loci after stringent multiple testing correction. A number of regions emerged as potentially interesting for follow-up at p < 1 × 10 −6, including SNPs in the genes FBXO47, ELOVL7, EDN1, and MAPT . Contrary to previous reports, we found no association of the genes SNCA and COQ2 with MSA. Conclusions: We present a GWAS in MSA. We have identified several potentially interesting gene loci, including the MAPT locus, whose significance will have to be evaluated in a larger sample set. Common genetic variation in SNCA and COQ2 does not seem to be associated with MSA. In the future, additional samples of well-characterized patients with MSA will need to be collected to perform a larger MSA GWAS, but this initial study forms the basis for these next steps.